If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -3) + 4y = 7 Reorder the terms: 3(-3 + y) + 4y = 7 (-3 * 3 + y * 3) + 4y = 7 (-9 + 3y) + 4y = 7 Combine like terms: 3y + 4y = 7y -9 + 7y = 7 Solving -9 + 7y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 7y = 7 + 9 Combine like terms: -9 + 9 = 0 0 + 7y = 7 + 9 7y = 7 + 9 Combine like terms: 7 + 9 = 16 7y = 16 Divide each side by '7'. y = 2.285714286 Simplifying y = 2.285714286
| 2x+34x=456 | | .05x-.08=.97 | | (2x+3x^2)=4 | | 0.25q+.05(9+q)=3.45 | | 2x+3(62.2)=11 | | 12x^2+18=174 | | 3m-150=495 | | 9(2m+1)+5(5m+3)=-62 | | 2.05+15x=2.35x | | 150m+3=495 | | 340=12x+40 | | 5-3x=21-7x | | 3(-98)+5y=17 | | .40g=.60 | | 2x+0=0.50x+16 | | 35x=10x+20 | | c-44=-12 | | .50E=.20 | | 3m-10=4m-13 | | 4(6x-7)-(3x-5)=50 | | v^2+9v-14=0 | | Y=x+y-x | | 5x-7=12.5 | | 3.14y=81.2004 | | 7+3m=-2 | | -13x^2+10x+10=-13X+46 | | 84x^2+68x-120=0 | | 4n^2-8n-21=0 | | .80=.5m | | 21-6(-4)=-11-14(-4) | | y=-2(x-7)(x+2) | | -28x+47=207 |